Generalised RAO test for polarimetric target detection - Lei Shen; Zhiwen Liu; Yougen Xu (The Journal of Engineering, 2019)
Here, a generalised Rao test method is presented for polarimetric multichannel adaptive signal detection. By introducing several tunable parameters into the Rao test detection statistics, the proposed polarimetric detector is quite general with the modified Rao test detector, the adaptive-matched filter detector, and the adaptive subspace detector being its special cases. The performance of the proposed polarimetric detector has been demonstrated with synthetic and real data. The results show that the new detector provides more flexibility of being adjustable than the current modified Rao test detector, against target steering vector mismatch.